Pengembangan Data Warehouse untuk Evaluasi Pembelajaran Matakuliah Berdasarkan Data Kuesioner Mahasiswa di SIAM dan Rekapitulasi Presensi Dosen (Studi Kasus Teknologi Informasi Fakultas Ilmu Komputer) - Juan Michel Hesekiel; Issa Arwani; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In order to make sure the quality of the learning process at Brawijaya University, students are asked to filling out some questionnaire. The questionnaire is filled out by students at the end of the semester online, at the University of Brawijaya (SIAM UB). Data from the questionnaire given by the head of the study program. The recapitulation data of teaching lecturers is also given by the head of the study program. But if you want to analyzed them the processing is still done manually. To obtain this information, a data collection mechanism from 2 or more integrated sources is needed. The data set will then be analyzed to be used as a source of reporting. The results of the analysis can be used as an evaluation for a study program. Therefore we need a solution that help the study program to analyzed data to the maximum. The solution that can be used for handling this kind of problems is data warehouse. To be able to have quality data that will be data warehouse, it needs the Extract, Transform, Loading (ETL) process. There are various kinds of software that handle ETL, one of them is Talend Open Studio. After the ETL is complete, using data visualization tool named Tableau a dashboard will be created. Based on the test results, verification of the ETL in the data warehouse tables was successfully done. The results of validation testing on the dashboard within the data warehouse also display valid status. Then also performed time testing on the ETL. The average time needed to execute ETL with a total of 4,625 rows is + 7 seconds.